Effects of Halal Awareness, Halal Certification, Brand Image, and Product Quality on Shoe Purchase Decisions - Santosa, Hadyan Jade; Muttaqin, Aminullah Achmad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze the influence of halal awareness, halal certification, brand image, and product quality on shoe purchasing decisions among Muslim consumers in Jakarta. Although awareness of halal products is increasing, attention to halalness in shoe products is still relatively limited. Therefore, this study was conducted to explore more deeply the factors that influence shoe purchasing decisions that are in accordance with sharia principles. The method used is a quantitative approach by distributing online questionnaires to respondents who are Muslim consumers in Jakarta who have purchased shoes in the past year. The sampling technique used purposive sampling with a total of 100 respondents. The data analysis technique used in this study is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the help of SmartPLS software. The results of this study are expected to provide theoretical contributions to the development of literature in the field of marketing, especially those related to Muslim consumer behavior in choosing halal fashion products. In addition, this study also provides practical insights for shoe industry players in developing marketing strategies that are in line with consumer religious values.